Age and education-matched cut-off scores for the revised German/Swiss-German version of ECAS. Issue 5 (17th August 2016) - Loose, Markus; Burkhardt, Christian; Aho-Özhan, Helena; Keller, Jürgen; Abdulla, Susanne; Böhm, Sarah; Kollewe, Katja; Uttner, Ingo; Abrahams, Sharon; Petri, Susanne; Weber, Markus; Ludolph, Albert C.; et al.
Abstract: The Edinburgh Cognitive and Behavioural ALS Screen (ECAS) has been developed to assess cognition and behaviour in patients with amyotrophic lateral sclerosis (ALS). Cognitive impairments of ALS-specific and ALS-non-specific functions can be determined using cut-off scores based on performance of healthy subjects. However, detailed analyses show that older healthy subjects perform worse than younger ones, whereas highly-educated individuals perform better than those with lower education levels. As a consequence, this study presents new age and education matched cut-off scores for the revised German/Swiss-German version of the ECAS based on the performance of 86 healthy subjects.